Wafer-scale layer transfer of GaAs and Ge onto Si wafers using patterned epitaxial lift-off. (12th February 2015) - Mieda, Eiko; Maeda, Tatsuro; Miyata, Noriyuki; Yasuda, Tetsuji; Kurashima, Yuichi; Maeda, Atsuhiko; Takagi, Hideki; Aoki, Takeshi; Yamamoto, Taketsugu; Ichikawa, Osamu; Osada, Takenori; Hata, Masahiko; et al.
Abstract: We have developed a wafer-scale layer-transfer technique for transferring GaAs and Ge onto Si wafers of up to 300 mm in diameter. Lattice-matched GaAs or Ge layers were epitaxially grown on GaAs wafers using an AlAs release layer, which can subsequently be transferred onto a Si handle wafer via direct wafer bonding and patterned epitaxial lift-off (ELO). The crystal properties of the transferred GaAs layers were characterized by X-ray diffraction (XRD), photoluminescence, and the quality of the transferred Ge layers was characterized using Raman spectroscopy. We find that, after bonding and the wet ELO processes, the quality of the transferred GaAs and Ge layers remained the same compared to that of the as-grown epitaxial layers. Furthermore, we realized Ge-on-insulator and GaAs-on-insulator wafers by wafer-scale pattern ELO technique.